The prevalence and behavioral risk factors contributing to non-communicable diseases in Bushbuckridge, Mpumalanga province, South Africa - Thabo D. Pilusa; Cairo B. Ntimana; Eric Maimela (Frontiers in Epidemiology)
BackgroundIntervention strategies such as health campaigns, pre-screening, health education, and health talks exist. Still, they are only active if there are outbreaks of the specific infectious disease not mainly NCDs. Therefore, there is a need to develop intervention strategies to improve the prevention and control of behavioral risk factors for NCDs by determining social, economic, and health system factors. Hence, the study aimed to determine the prevalence and determinants of behavioral risk factors contributing to NCDs in Bushbuckridge, South Africa.MethodsThis cross-sectional descriptive study involved 2,400 respondents selected from healthcare facilities. The participants were selected using simple random sampling. Data was analyzed using SPSS version 29. A comparison of proportions was performed using the chi-square test. The association between sociodemographic and lifestyle factors with predictors of behavioral risk factors for NCD was analyzed using binary regression analysis, and the statistical significance was set at a p-value of <0.05.ResultsThe mean age of the study was 46.27 ± 13.38. The prevalence of Smoking was 51.3% (1,211). The prevalence of alcohol consumption within the past year was 19.3% (463), while inadequate fruit and vegetable intake was 76.2%. Physical inactivity was 97.2%. Additionally, hypertension and diabetes were 51% and 50.1% respectively. Participants (≥35 years) were likely to have low fruit and vegetable intake (aOR = 1.3; 95% CI: 0.99–1.62). Widows were 30% less likely to smoke (aOR = 0.72; 95% CI: 0.57–0.92), yet they were 1.4 times more likely to consume alcohol (aOR = 1.4; 95% CI: 0.99–1.84). Unemployed participants were found to have a higher likelihood of consuming alcohol (aOR = 1.3; 95% CI: 1.02–1.54).ConclusionThe prevalence of behavioral risk factors for NCDs was found to be high among rural populations residing in Bushbuckridge, underscoring the need for sustained and comprehensive interventions. In rural areas like Bushbuckridge, the combination of poverty, unemployment, limited healthcare access, and evolving social dynamics creates a challenging environment that fosters unhealthy behaviors and increases the risk of NCDs. To effectively reduce the burden of these diseases in such communities, public health strategies must focus on socio-economic and cultural determinants, rather than just demographic factors.